Evaluasi Penggunaan Obat Antihipertensi Pada Pasien Hipertensi Primer Rawat Jalan Lanjut Usia Periode Januari 2022 – Juli 2023 Di RSUD Arifin Achmad Provinsi Riau - Nawwar Irfan; Ayu Rahmawati; Nurbaiti; Aulia Fitri, Windy (The Journal Of Pharmacy, 2023)
Hypertension is a condition where the increase in systolic blood is above the normal limit, which is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg. The purpose of this study was to determine the sociodemographic relationship to the treatment outcomes of hypertensive patients and to examine patterns of antihypertensive drug use at Arifin Achmad Hospital, Riau Province. The method used in this study was an observational descriptive method using retrospective data which was carried out by recording medical record data and the research subjects used in this study were outpatients with a diagnosis of hypertension with a total sample of 90 elderly patients. The results of this study showed that the most data on patient characteristics, namely female sex, amounted to 66 people (73.3%) and the most widely used drug class, namely amlodipine, was 76 patients (62.3%). On the results of the chi-square test with a significance value of p value = 0.05 for the relationship between age and gender for risk factors, the age value was p = 0.123 while gender had a p value = 0.000. It was concluded that the evaluation of antihypertensive drugs was 100% correct and showed that age and risk factors had no relationship, while gender had a relationship with risk factors.